Pengaruh Komunikasi Internal dan Work Culture Terhadap Optimalisasi Kinerja Tenaga Pendidik di SD Islam Teratai Putih Global - Irdhina, Della Hanifatul; Puspasari, Aprilia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the influence of internal communication and work culture on optimizing the performance of educators at SD Islam Teratai Putih Global. The approach method in this study uses a quantitative method with data collection through distributing questionnaires. The population in this study were all educators at SD Islam Teratai Putih Global, totaling 65 people, and all of them were used as research samples using saturated sampling techniques. The data analysis techniques used were data quality testing, classical assumption testing, hypothesis testing, and determination coefficient testing, which were carried out using SPSS 27. The results of the analysis showed that internal communication had a positive and significant effect on the performance of educators partially with a t-count of 2,640 t-table 1,999 and a significance of 0.010 0.05. Work culture also had a positive and significant effect on the performance of educators with a t-count of 4,816 1,999 and a significance of 0.001 0.05. Simultaneously, internal communication and work culture have a positive and significant effect on the performance of educators with a calculated f value of 27.281 f table 3.15 and a significance of 0.001 0.05.